Klub Marynarza zaprasza na wielką zabawę karnawałową. (Gdynia : [s.n.], 1947)
Afisz inf. o zabawie 11.01.1947 r.
Keywords: Sopot (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- źródła